A Train Driving Simulator to Enhance Railway Technology Student’s Learning Experience Using Prototype Method and OpenBVE - Domato, Mea Ann E. Domato Ann E.; Gutierrez, Gabriel T.; Canas, Maxine Honey A; Salinas, Cyril Rose R.; Sison, Venerando A.; Bunag, Sherlie D.; Delizo, Carlo Jay G.; Aunario, Connie C.; Andador, Jennifer D.; Garcia, Julius G. (LPPM STIKI Malang, 2024)
A Train Driving Simulator is a software application that tries to replicate the experience of operating a train. This unique equipment minimizes the expense of using actual rolling stock to teach future railway staff. The research aims to create a Train Driving Simulator with OpenBVE for Railway Technology students. The research focused on making a simulator that simulates the feeling of driving a train, which involved detailed physics modeling and control of the train. The simulator was built to be user-friendly and accessible, with features such as the 3D representation of the LRT Line 1 route and its compact, portable architecture. The simulator was built from commercial off-shelf parts and tested for usefulness, safety, and durability. The simulator's performance was tested using the TUP evaluation metrics. The research aimed to enhance the learning experience of students undergoing railway technology by providing on-site training in operating a train. The simulator will likely provide students and instructors with maximum benefit in courses like Railway Signaling, Rolling Stocks, and Railway Facilities